Can Mozart Improve Weight Gain and Development of Feeding Skills in Premature Infants? A Randomized Trial - Lafferty, Margaret A.; Mackley, Amy; Green, Pam; Ottenthal, Deborah; Locke, Robert; Guillen, Ursula (American Journal of Perinatology, 2021)
Objective The study aimed to assess in a prospective randomized study the effect of Mozart's music on time to regain birth weight (BW) and development of oral feeding skills in babies born between 280/7 and 316/7 weeks of gestation.Study Design Healthy premature infants born between 280/7 and 316/7 completed weeks of gestation were randomized within 3 days of birth to either music or no music exposure. Infants in the music group were exposed to Mozart's double piano sonata twice per day for 14 days. The primary outcome was time to regain birth weight. The secondary outcome was development of oral feeding skills as evaluated by a speech/language pathologist blinded to the intervention. We hypothesized that exposure to Mozart's double piano sonata would decrease time to regain BW and improve feeding skills. A total of 32 newborns were needed to detect a 3-day difference in time to regain BW.Results Forty infants were enrolled and randomized. There were no significant differences between the two groups regarding the time to regain BW (p = 0.181) and the time to achievement of full oral feeds (p = 0.809).Conclusion Exposure to Mozart's double piano sonata for 14 days after birth did not significantly improve time to regain BW or time to achieve full oral feedings in very premature infants. It is possible that Mozart's music has no effect or that the duration of music exposure was not sufficient to have a physiologic effect on growth and oral feeding skills.Key Points
Keywords: neonate; music; feeding; weight gain